Luteoporia tenuissima sp. nov. (Polyporales, Basidiomycota), evidenced by morphological characteristics and phylogenetic analysis - Luo, Kai-Yue; Yuan, Yuan; Liu, Hong-Gao; Ghobad-Nejhad, Masoomeh; Dai, Yu-Cheng (Phytotaxa, 2024)
A new poroid wood-inhabiting fungus in the Polyporales, Luteoporia tenuissima, from southwest China, is described based on morphological and molecular evidence. Luteoporia tenuissima is characterized by annual, resupinate basidiomata with lemon chrome pores when fresh, becoming cinnamon buff when dry, tissues becoming purple in KOH, a monomitic hyphal system, generative hyphae thick-walled and bearing clamp connections, and ellipsoid, smooth basidiospores measuring 2.9–3.8 × 1.9–2.4 µm. The phylogenetic analysis based on ITS + nLSU rDNA sequences shows that the new species belongs to Luteoporia, forming a monophyletic lineage with strong support, clustering with L. albomarginata and L. citriniporia. Both morphological characteristics and molecular phylogeny confirm the placement of the new species within the genus Luteoporia. A full description, illustration, phylogeny of the new species, and comparisons with morphologically similar or phylogenetically related species are provided. In addition, an identification key is provided for the currently known Luteoporia species.